2018
DOI: 10.1016/j.cels.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Trajectory Analysis of Single-Cell RNA-Seq and Imaging Data Reveals Alternative Tuft Cell Origins in the Gut

Abstract: Summary Modern single-cell technologies allow multiplexed sampling of cellular states within a tissue. However, computational tools that can infer developmental cell-state transitions reproducibly from such single-cell data are lacking. Here, we introduce p-Creode, an unsupervised algorithm that produces multi-branching graphs from single-cell data, compares graphs with differing topologies, and infers a statistically robust hierarchy of cell-state transitions that define developmental trajectories. We have ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
181
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(187 citation statements)
references
References 74 publications
(144 reference statements)
1
181
3
2
Order By: Relevance
“…p-Creode allows for pseudo-temporal ordering that depicts progression relationships (Herring et al, 2018). This analysis revealed that progenitors progressively lose Neurog3 expression while gaining β- or α-cell features in two separate trajectories (Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…p-Creode allows for pseudo-temporal ordering that depicts progression relationships (Herring et al, 2018). This analysis revealed that progenitors progressively lose Neurog3 expression while gaining β- or α-cell features in two separate trajectories (Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 3,368 cells were sequenced with, on average, 5,886 unique transcripts per cell (as measured by number of UMIs) identified from, on average, 56,343 reads per cell. Sequencing data were mapped, quantified, and normalized following the protocol of our previous report (Herring et al, 2018). …”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell encapsulation of gut epithelial tissue was performed using the inDrop platform (1CellBio) with an in vitro transcription library preparation protocol, as previously described (46,47). inDrop utilizes CEL-Seq in preparation for sequencing and is summarized as follows: (1) reverse transcription (RT), (2) ExoI nuclease digestion, (3) SPRI purification (SPRIP), (4) second strand synthesis, (5) SPRIP, (6) T7 in vitro transcription linear amplification, (7) SPRIP, Approximately 3,000 cells for each sample entered the microfluidic chip.…”
Section: Indrop Single-cell Rna-seqmentioning
confidence: 99%
“…TSCAN first clusters the data, then like Monocle infers a tree from the data (Ji & Ji, ). p‐Creode fits multiple trees to the data, uses the data to smooth them, then identifies the tree which is most central within these (Herring et al , ). These algorithms can all (with the exception of SCUBA, which requires time annotations) return branch points regardless of the actual evidence in the data, and any decision on the presence or absence of a branch point must be made by the user.…”
Section: Introductionmentioning
confidence: 99%